Gambaran Kecemasan Pasien Preoperatif Sectio Caesarea dengan anestesi spinal di RSIA Siti Hawa Padang - Rani Ilma Imani; Muhammad Zulfadli Syahrul; Dedy Kurnia (Fakultas Kedokteran, Universitas Andalas, 2020)
Anxiety is a response to a threat that comes nowhere, internally, indistinctly or conflictually. One common cause of the anxiety in the world is a patient that will experience an operation. The incidence is about 11-80% in the world. There are some risk factors that impact the anxiety of pre-operative patient like ages, education levels, operation histories, information resources, and etc. This study aimed to give the incidence of the anxiety of cesarean section pre-operative patients with spinal anaesthesia at Siti Hawa’s Mother and Child Hospital Padang. Specifically, cesarean section is chosen to be observed because this surgery is the most common operation in the world and spinal anesthesia is the main choice because of its rapid onset and low failure. This study was an observational-descriptive with cross-sectional design done from July until August 2018. Data were collected by direct interview with eighty-three respondents using The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. This result of this study based on APAIS questionnaire were (51,8%) patients does not feel anxiety and the most need for information was low (48,2%). The highest frequency of preoperative anxiety were patients twenty to thirty-five years old (54%), based on education levels (62,9%) patients graduated from college, based on operation histories (63%) patients that hadn’t experience the operation yet, and based on the information resources (53,3%) patients who had known the operation procedure.